1995
DOI: 10.1073/pnas.92.20.9353
|View full text |Cite
|
Sign up to set email alerts
|

A membrane-associated form of sucrose synthase and its potential role in synthesis of cellulose and callose in plants.

Abstract: Sucrose synthase (SuSy; EC 2.4.1.13; sucrose + UDP = UDPglucose + fructose) has always been studied as a cytoplasmic enzyme in plant cells where it serves to degrade sucrose and provide carbon for respiration and synthesis of cell wall polysaccharides and starch. We report here that at least half of the total SuSy of developing cotton fibers (Gossypium hirsutum) is tightly associated with the plasma membrane. Therefore, this form of SuSy might serve to channel carbon directly from sucrose to cellulose and/or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
392
1
13

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 577 publications
(422 citation statements)
references
References 44 publications
16
392
1
13
Order By: Relevance
“…It has been suggested that UDPglucose for the synthesis of cell wall components is supplied via a specific association between SUS and cell wall biosynthetic enzymes (Amor et al, 1995;Verma and Hong, 2001;Salnikov et al, 2003;Persia et al, 2008). SUS is frequently associated with plasma membranes, consistent with the idea that it supplies UDPglucose to either cellulose synthase or callose synthase or both.…”
Section: Callose Synthesis In the Phloem May Differ From That In Othementioning
confidence: 52%
“…It has been suggested that UDPglucose for the synthesis of cell wall components is supplied via a specific association between SUS and cell wall biosynthetic enzymes (Amor et al, 1995;Verma and Hong, 2001;Salnikov et al, 2003;Persia et al, 2008). SUS is frequently associated with plasma membranes, consistent with the idea that it supplies UDPglucose to either cellulose synthase or callose synthase or both.…”
Section: Callose Synthesis In the Phloem May Differ From That In Othementioning
confidence: 52%
“…starch [7] and cell wall synthesis [3]. A positive correlation between sucrose synthase activity, sink strength and sucrose import has been demonstrated in many sink organs, suggesting a role for this enzyme in carbohydrate partitioning between sink and source organs [24,28,30].…”
Section: Introductionmentioning
confidence: 98%
“…such as the synthesis of cell wall [11] and starch [12,13]. In young leaves (sink tissue), Sus has supposedly a role in breaking down sucrose imported from mature leaves (source tissue).…”
Section: Introductionmentioning
confidence: 99%